Hukum Ekonomi: Analisis dan Implementasi Dalam Konteks Global - Robby Nurtresna; Mabsuti Mabsuti; Sopiyati Sopiyati; Ogi Charis M. Arifin; Faiq Faiq; Anisa Nurul Hidayah; Rizka Sepriyanti; Asep Guntur; Tryola Nadia (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Economic law is a branch of law focused on regulating and overseeing economic activities, encompassing various fields such as corporate law, international trade, investment, competition, and consumer protection. In the era of globalization, the role of economic law becomes increasingly critical in creating economic stability and justice among nations. This study aims to analyze the role of economic law in regulating global economic activities, identify challenges and opportunities in its implementation, and provide policy recommendations to strengthen the application of economic law in various countries. Using a qualitative approach with document analysis methods, this research finds that power imbalances, transparency, corruption, and adaptation to technological changes are the main challenges in the implementation of economic law. However, opportunities to enhance the effectiveness of economic law exist through the strengthening of legal institutions, increased international cooperation, and the adoption of new technologies. The ASEAN case study shows that regional cooperation and free trade agreements can create a more open and competitive economic environment, despite ongoing challenges. This study concludes that economic law plays a crucial role in regulating and overseeing global economic activities and provides policy recommendations to improve its effectiveness.